Correction: Design and expression of a chimeric recombinant antigen (SsIR-Ss1a) for the serodiagnosis of human strongyloidiasis: Evaluation of performance, sensitivity, and specificity. - Mostafa Omidian; Zohreh Mostafavi-Pour; Marzieh Asadi; Meysam Sharifdini; Navid Nezafat; Ali Pouryousef; Amir Savardashtaki; Mortaza Taheri-Anganeh; Fattaneh Mikaeili; Bahador Sarkari (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0012320.].